2020
DOI: 10.1111/jfbc.13526
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of peroxidases from garden cress sprouts and their roles in lignification and removal of phenol and p ‐chlorophenol

Abstract: The study aims to evaluate the relation between peroxidases of day-6 garden cress sprouts and phenolic compounds. Three cationic, three anionic, and two unbounded peroxidases were separated from day-6 garden cress sprouts. Cationic (GCP1) and anionic (GCP2) peroxidases were purified with molecular masses of 25 and 40 kDa, respectively. The K m values of GCP1 toward H 2 O 2 and guaiacol were lower than GCP2. The anionic GCP2 exhibited high affinity toward some lignin monomers, sinapyl alcohol, coniferyl alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Chlorophenol is a kind of toxic organic pollutant with liposolubility and bioaccumulation, which has been listed as one of the 68 kinds of water pollutants in China [1][2][3]. At present, the main methods to deal with chlorophenols in water are the biological method, microbial fuel cell method, and so on [4][5][6][7]. Photocatalysis is an effective and environmentally friendly environmental purification technology, which can decompose toxic chlorophenols into CO 2 , H 2 O, and non-toxic inorganic acids under sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophenol is a kind of toxic organic pollutant with liposolubility and bioaccumulation, which has been listed as one of the 68 kinds of water pollutants in China [1][2][3]. At present, the main methods to deal with chlorophenols in water are the biological method, microbial fuel cell method, and so on [4][5][6][7]. Photocatalysis is an effective and environmentally friendly environmental purification technology, which can decompose toxic chlorophenols into CO 2 , H 2 O, and non-toxic inorganic acids under sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 36 reported that during the seed germination the carbohydrates, proteins and cell wall conjugated-phenolic compounds are degraded and lead to increase the simple sugars, free amino acids and free/soluble phenolic compounds. This examination could clarify the increase of total phenolic and flavonoid contents in mustard sprouts.The decline in the total phenolic content of mustard sprouts after 5 days of germination may be attributed to convert of some free phenolic compounds to bound phenolic compounds and/or they consumed in lignin synthesis 37 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The PPO, CAT and POD catalyzed the oxidation and generation of phenolic compounds and consumption of H 2 O 2 51 54 .The highest activity of POD on 5-days sprouts indicated a high correlation between this enzyme and the highest phenolic and flavonoid levels on the same day. The POD is critical in the polymerization of mono- and di-phenols for the formation of polyphenols/phenolics and the activation of antioxidants during the germination process 40 .This may explain the association between the increase in POD enzyme activity and the increase in the concentration of polyphenols in 5-days mustard sprouts. Similarly, the phenolic content of green gram sprouts was associated with an increase in POD activity 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, increasing Hg accumulation in garden cress shoots was correlated with an increase in POD activity and changes in total carotenoid content 19 . Furthermore, POD participates in the polymerization of phenolic compounds for lignin synthesis to build a barrier that protects against toxic metal ions 49 .
Figure 1 Effect of Cd and Pb at different concentrations (25-150 mg kg −1 ) on the activities of the antioxidant enzymes: ( A ) POD, ( B ) CAT, ( C ) GST, and ( D ) GR of GCS.
…”
Section: Resultsmentioning
confidence: 99%